Short-term effects of intravitreal anti-vascular endothelial growth factor agents on body weight and multiple systems after treatment for retinopathy of prematurity - Chen, Jing; Hao, Qingfei; Zhang, Jing; Du, Yanna; Chen, Haoming; Cheng, Xiuyong (Frontiers in Pediatrics, 2023)
Objectives This study's goal was to assess the short-term effect on body weight and multiple systems following intravitreal injections of ranibizumab and aflibercept for retinopathy of prematurity (ROP). Methods We retrospectively assessed infants with ROP who received intravitreal anti-vascular endothelial growth factor agents (VEGF) treatment at our hospital. They were classified into 2 groups based on the drugs administered: the intravitreal ranibizumab (IVR) group and the intravitreal aflibercept (IVA)group. The body weight (BW) gains for the pre-treatment week, the 1st week after treatment, and the 2nd week after treatment were compared for each group. Additionally, other parameters such as blood pressure, heart rate, oxygen concentration, volume of milk and output of urine at four time points were also measured. We used repeated measurement analysis of variance analyzed these data. Results In total, 95 preterm infants were recruited, including 51 cases in the IVR group and 44 cases in the IVA group. The BW gain for the 1st week after treatment was significantly lower than the pre-treatment week in each group (P<0.05), while there was no decrease in weekly BW gain in the 2nd week after treatment compared with that pre-treatment week. Based on the comparison between groups, the BW gain in the IVR group was significantly higher than in the IVA group in the second post-treatment week. Repeated measurement analysis of variance showed that there were no significant differences in blood pressure, heart rate, oxygen concentration, volume of milk and output of urine in both groups over time. Conclusions IVR and IVA could have a short-term inhibitive effect on body weight gain in infants after treatment for ROP, whereas there is no significant impact on other systems.